2022
DOI: 10.1177/03611981221083616
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Main Environmental Impact Categories Over the Life Cycle of Hot Mix Asphalt: An Application to Green Public Procurement

Abstract: Increased environmental awareness has led road agencies to consider the implementation of green public procurement (GPP). Besides sustainability rating systems, environmental indicators can also be implemented in GPP to help road agencies make informed decisions about the environmental impact of the pavement works they procure. A vast literature review revealed that it is still unclear which impact categories are responsible for the majority of the total environmental impact of asphalt mixtures. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Several studies have already addressed the environmental impacts of roads and pavements. A commonly used method for this purpose is Life Cycle Assessment (LCA) [18,19]. LCA is a robust and standardized method for assessing the environmental impacts of products and services throughout their life cycle and is widely used both in industry and academia [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already addressed the environmental impacts of roads and pavements. A commonly used method for this purpose is Life Cycle Assessment (LCA) [18,19]. LCA is a robust and standardized method for assessing the environmental impacts of products and services throughout their life cycle and is widely used both in industry and academia [20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the EOL impact (C1-C3) is the impact from the deconstruction, transport of waste, and waste processing phase. These results highlight the importance of modeling entire pavement sections rather than individual layers in pavement sustainability assessment.Regarding midpoint indicators, a prior study showed that at least 90% of the total impact in the cradleto-cradle analysis of hot mix asphalt is explained by only four indicators: global warming (GWP), fine particulate matter formation (FPMF), fossil resource scarcity (FRS), and human non-carcinogenic toxicity (HNCT)[55]. Following the same approach, this study found that five out of the 18 midpoint indicators considered in ReCiPe 2016 (H) are responsible for more than 95% of the total environmental impact of the different materials evaluated (Figure8a).…”
mentioning
confidence: 99%